2021
DOI: 10.3389/fmicb.2021.669709
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Lipid Chain Length of a Membrane-Permeabilizing Lipopeptide Results From the Balance of Membrane Partitioning and Local Damage

Abstract: Pseudodesmin A (PSD) is a cyclic lipodepsipeptide produced by Pseudomonas that kills certain bacteria at MIC1/2 in the single micromolar range, probably by permeabilizing their cellular membranes. Synthetic PSD variants, where the native decanoic (C10) acyl chain is varied in length from C4 to C8 and C12 to C14 carbons, were described to be not or less active against a panel of gram-positive strains, as compared to native PSD-C10. Here, we test the membrane-permeabilizing activity of PSD-C4 through PSD-C14 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 64 publications
(107 reference statements)
0
22
0
Order By: Relevance
“…This protocol requires a validation because it does not a priory eliminate the possibility of transient local peptide concentration differences, which might cause enhanced leakage or equilibrate only slowly once the peptide is bound anywhere. Fortunately, for pseudodesmin, this validation excluding mixing errors has been carried out already in a previous study (45), showing leakage errors due to slow peptide redistribution (occurring on a minute timescale (<30 min)) to be of maximum 5 10%.…”
Section: Quantification Of Calcein Leakage By Tcspcmentioning
confidence: 82%
See 3 more Smart Citations
“…This protocol requires a validation because it does not a priory eliminate the possibility of transient local peptide concentration differences, which might cause enhanced leakage or equilibrate only slowly once the peptide is bound anywhere. Fortunately, for pseudodesmin, this validation excluding mixing errors has been carried out already in a previous study (45), showing leakage errors due to slow peptide redistribution (occurring on a minute timescale (<30 min)) to be of maximum 5 10%.…”
Section: Quantification Of Calcein Leakage By Tcspcmentioning
confidence: 82%
“…Calcein release from calcein-LUVs (i.e., membrane permeabilization) triggered by the CLiP viscosin, pseudodesmin A, or viscosin-E2K was measured via time-correlated single-photon counting (TCSPC) with a FluoTime 100 spectrometer (PicoQuant, Berlin, Germany) as described (44,45). The fundamentals of TCSPC are discussed comprehensively elsewhere (46).…”
Section: Quantification Of Calcein Leakage By Tcspcmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, the natural decanoic (C10) pseudodesmin (pdm) was shown to be more active against a panel of Gram-positive bacteria strains in comparison with synthesized pdm C4 to C8 and C12 to C14. In a recent study, the membrane-permeabilizing activity of natural pdm was compared with those of the aforementioned synthetic variants [131]. By employing the fluorescence lifetime leakage assay (a technique used to assess calcein release from liposomes), it was shown that antagonistic concentrations and chain length dependence correlate with liposome leakage and antimicrobial activity.…”
Section: Pseudomonasmentioning
confidence: 99%